Forest area affected by fires in Mexico: Initial notes toward a preventive management model - González-Rosales, Andrés (2022)
[Introduction]: The Forest Area Affected by Fires (FAAF) could be explained by variables that that although they are intuitively known, they have not been quantified to estimate their importance in preventing the fight of forest fires. [Objective]: To propose a statistical model that demonstrates implicated factors on SAAF and thereby provide initial information for the strengthening of a fire prevention scheme. [Methodology]: Were applied two statistical techniques 1) principal component analysis, was used to justify the variables; and, 2) panel data analysis was used to understand the relationship between intuitive variables on detection, arrival and duration, on the affected surface. [Results]: The results indicate that 11 states of Mexican Central-Western Region there is a relationship between the Quantity and Duration of forest fires, more than proportional for the Quantity of Fires (1.28) and less than proportional with the Duration of these (0.52), in relation to the FAAF. [Conclusions]: This model can have applications in the planning of actions and schemes for the protection and prevention of forest ecosystems and the allocation of resources (human, equipment, and materials) more effective and efficient to prevent and reduce forest fires.